2012
DOI: 10.1002/jsfa.5888
|View full text |Cite
|
Sign up to set email alerts
|

Organic food quality: from field to fork

Abstract: UDP‐galactose mutase is a flavoenzyme that catalyzes the isomerization of UDP‐galactopyranose into UDP‐galactofuranose, a key step in the biosynthesis of important bacterial oligosaccharides. Several mechanisms for this unique ring‐contraction have been proposed, one of them involving a putative 1,4‐anhydrogalactopyranose as an intermediate in the reaction. The purpose of this study was to probe the mutase binding site with conformationally restricted analogues of its substrate. Thus, we describe the straightf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For this reason, the organic sector must keep high quality standards and provide verifiable and realistic information about in which value-added categories organic food is supported by substantial research and in which categories the support is not (yet) evident. In addition to the authentication and regulation of farming practices, transparency on realistic organic benefits will safeguard organic integrity throughout the supply and consumption chain (Kahl 2012).…”
Section: Food Quality and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the organic sector must keep high quality standards and provide verifiable and realistic information about in which value-added categories organic food is supported by substantial research and in which categories the support is not (yet) evident. In addition to the authentication and regulation of farming practices, transparency on realistic organic benefits will safeguard organic integrity throughout the supply and consumption chain (Kahl 2012).…”
Section: Food Quality and Healthmentioning
confidence: 99%
“…One of the major challenges for the organic agri-food system is to change the fieldwork-driven Organic 2.0 groundwork to an Organic 3.0 methodology that uses information from a broad sector of conducted research, consumer interest and sustainable consumption as a driver of organic growth (weeding) (Kahl et al 2010;Kahl 2012). Organic 3.0 will include information on value-added components of organic food and farming and will be supported by the rapid increase in data available to perform meta-analyses comparing levels of relevant compounds in organic and non-organic products (e.g.…”
Section: Product Quality and Human Healthmentioning
confidence: 99%
“…Both in theoretical research and empirical research, it is shown that organic food industries in Europe, America and other countries had quite complete systems [5]. Although there were differences in the degree of development, market operation and market management of organic food industry in developed countries are characterized by standardized operation, strict management and perfect industrial system of organic food market [6]. The theoretical research on organic food was more in-depth and systematic, forming a relatively complete theoretical system in the aspects of organic food consumer behavior, market competition, policy support and so on.…”
Section: Introductionmentioning
confidence: 99%
“…After the great success of the first event on this topic in Prague 2011, where the different research questions and approaches on organic food quality research were brought together (see the Special Issue published in JSFA in 2012 ), the second event marked a new step towards identified major research goals.…”
mentioning
confidence: 99%